Particulate matter air pollution components and risk for lung cancer. (February 2016) - Raaschou-Nielsen, O.; Beelen, R.; Wang, M.; Hoek, G.; Andersen, Z.J.; Hoffmann, B.; Stafoggia, M.; Samoli, E.; Weinmayr, G.; Dimakopoulou, K.; Nieuwenhuijsen, M.; Xun, W.W.; et al.
Abstract: Background: Particulate matter (PM) air pollution is a human lung carcinogen; however, the components responsible have not been identified. We assessed the associations between PM components and lung cancer incidence. Methods: We used data from 14 cohort studies in eight European countries. We geocoded baseline addresses and assessed air pollution with land-use regression models for eight elements (Cu, Fe, K, Ni, S, Si, V and Zn) in size fractions of PM2.5 and PM10 . We used Cox regression models with adjustment for potential confounders for cohort-specific analyses and random effect models for meta-analysis. Results: The 245, 782 cohort members contributed 3, 229, 220 person–years at risk. During follow-up (mean, 13.1 years), 1878 incident cases of lung cancer were diagnosed. In the meta-analyses, elevated hazard ratios (HRs) for lung cancer were associated with all elements except V; none was statistically significant. In analyses restricted to participants who did not change residence during follow-up, statistically significant associations were found for PM2.5 Cu (HR, 1.25; 95% CI, 1.01–1.53 per 5 ng/m 3 ), PM10 Zn (1.28; 1.02–1.59 per 20 ng/m 3 ), PM10 S (1.58; 1.03–2.44 per 200 ng/m 3 ), PM10 Ni (1.59; 1.12–2.26 per 2 ng/m 3 ) and PM10 K (1.17; 1.02–1.33 per 100 ng/m 3 ). In two-pollutant models, associations between PM10 and PM2.5 and lung cancer were largely explained by PM2.5 S. Conclusions: This study indicates that the association between PM in air pollution and lung cancer can be attributed to various PM components and sources. PM containing S and Ni might be particularly important. Highlights: Particulate matter air pollution is a human lung carcinogen. The particulate matter components being responsible have not been identified. This study indicates that various components are responsible. The sulfur and nickel containing particles might be particularly important.